10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
The Veterans Health Administration (VHA) has been a beacon of what team integration including a clinical pharmacist can do to improve patient care. The VHA is the largest integrated health care system in the United States. Clinical Pharmacist Practitioners (CPP) operate under a scope of practice that allows for initiation, discontinuation, and modification of medication therapies in patients with a confirmed diagnosis as part of providing comprehensive medication management (CMM). Standardization related to the "what" and the "how" CMM is practiced within the VHA have enabled the expansion of clinical pharmacy practice. While variation exists across the country, within the VHA the core components of CPP practice are established through policy and process. Having a standardized credentialing process identical to other non-pharmacy providers and having that process written in policy allows for less variation from facility to facility.